Prevalence of JAK2V617F, CALR in Philadelphia Positive and Negative Myeloproliferative Neoplasm: - Ramzi, Mani; Abedi, Elham; Karimi, Mehran; Cohan, Nader; Haghpanah, Sezaneh; Yaghobi, Ramin; Azarpira, Negar; Moghadam, Mohamad; Bayat, Elahe; Farokhian, Farnoush; Mohammadi, Hamid; Razmara lak, Elahe; et al. (Galen Medical Journal, 2021)
Background: Myeloproliferative neoplasms (MPNs) are heterogeneous disorders with a variety of genetic abnormalities. We aim to assess the prevalence of Calreticulin (CALR) and JAK2 mutations in Iranian MPNs. Materials and Methods: In a cross-sectional study, CALR and JAK2 mutations among 130 MPNs patients, including 78 Philadelphia chromosome-negative (MPN-) and 52 Philadelphia chromosome-positive (MPN+) as well as 51 healthy control subjects, were investigated by GAP-PCR. Results: In MPN- group JAK2 and CALR gene mutations were found in 64.1% and 7.7%, respectively, that 5.1% were positive for both mutations, and 2.6% had only CALR mutation. In polycythemia vera (PV) patients 90% had JAK2 mutation, which was significantly higher than other MPN- or MPN+ patients. Most of the MPN+ patients had neither mutation in CALR nor JAK2 (70% CALR-/JAK2-). Among all patients’ groups, the prevalence of CALR+ mutation in either rs1450785140 (4 cases) or rs765476509 (5 cases) position was not statistically different. Conclusion: These results showed a low prevalence of CALR mutations in all types of MPNs in the Iranian population that its frequency may influence by ethnicity and genetic diversity. CALR mutation may be seen in JAK2 negative cases, also. The PV had the highest JAK2 mutation with a 90 percent positivity rate among MPNs cases. [GMJ.2021;10:e2127]